2012
DOI: 10.1177/2047487312462799
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced changes of left ventricular diastolic function in postmenopausal amateur marathon runners: assessment by echocardiography and cardiac biomarkers

Abstract: 2D strain analysis of the left and right ventricles showed an acute improvement of the systolic function after marathon running in pre- and postmenopausal well-trained women. There were no long lasting detrimental effects on the diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
(31 reference statements)
3
19
0
1
Order By: Relevance
“…Moreover, we demonstrated a small increase in other parameters of LV systolic function (i.e. LV strain and SmLV) as previously described [22]. Therefore, we found no evidence of an overall decline in LV function after exercise.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, we demonstrated a small increase in other parameters of LV systolic function (i.e. LV strain and SmLV) as previously described [22]. Therefore, we found no evidence of an overall decline in LV function after exercise.…”
Section: Discussionsupporting
confidence: 54%
“…Exercises that are appropriate and specific at the rhythm can provide better production and functioning of the testosterone hormone secreted by the body. On the contrary, it is stated that overdose cardio exercise may decrease the testosterone level (12,18). When testosterone supplementation is taken with the level of tetstosterone increased by exercise, it causes more harm than good in the body (16).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 21 accepted the invitation. The patients were asked to avoid physical exercise the day before the examination because earlier studies have shown that physical exercise or hard physical training can cause increased hs-cTnT levels [13]. Follow-up was performed at the PHC centre where the patient had chosen to be listed.…”
Section: Methodsmentioning
confidence: 99%